2021
DOI: 10.1038/s41563-021-01108-x
|View full text |Cite
|
Sign up to set email alerts
|

Microtubules tune mechanosensitive cell responses

Abstract: Mechanotransduction is a process by which cells sense the mechanical properties of their surrounding environment and adapt accordingly to perform cellular functions such as adhesion, migration and differentiation. Integrin-mediated focal adhesions are major sites of mechanotransduction and their connection with the actomyosin network is crucial for mechanosensing as well as the generation and transmission of forces onto the substrate. Despite having emerged as major regulators of cell adhesion and migration, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 58 publications
3
109
0
Order By: Relevance
“…Much is known about the synergistic nature of microtubules and actomyosin activity. Indeed, non-muscle myosin II has been shown to suppress microtubule growth in order to stabilise cell morphology ( Sato et al, 2020 ), whilst microtubule acetylation has been found to regulate actomyosin-derived force generation ( Joo and Yamada, 2014 ; Seetharaman et al, 2021 ). Actomyosin and microtubule cross-talk also regulates morphology during differentiation and cell migration in a variety of cell types ( Akhshi et al, 2014 ; Wu and Bezanilla, 2018 ; Seetharaman and Etienne-Manneville, 2020 ), suggesting that communication between these mechanical networks is fundamentally important in determining VSMC morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Much is known about the synergistic nature of microtubules and actomyosin activity. Indeed, non-muscle myosin II has been shown to suppress microtubule growth in order to stabilise cell morphology ( Sato et al, 2020 ), whilst microtubule acetylation has been found to regulate actomyosin-derived force generation ( Joo and Yamada, 2014 ; Seetharaman et al, 2021 ). Actomyosin and microtubule cross-talk also regulates morphology during differentiation and cell migration in a variety of cell types ( Akhshi et al, 2014 ; Wu and Bezanilla, 2018 ; Seetharaman and Etienne-Manneville, 2020 ), suggesting that communication between these mechanical networks is fundamentally important in determining VSMC morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we observed that global activation of GEF-H1-RhoA axis induced actin polymerization outside of the synapse, independently of myosin II activity. Interestingly, it was recently shown that microtubules were acetylated in the vicinity of the centrosome upon immune synapse formation, resulting in the local release and activation of GEF-H1 (27, 30). Our results suggest that GEF-H1 might activate RhoA to trigger downstream formin-dependent actin nucleation at the immune synapse exclusively.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that GEF-H1 might activate RhoA to trigger downstream formin-dependent actin nucleation at the immune synapse exclusively. In this model, RhoA would remain inactive in the rest of the cell, most likely due to GEF-H1 trapping on microtubules deacetylated by HDAC6 (30, 31). We suggest that this “local activation” of GEF-H1 and “global inhibition” by trapping is a reminiscent of the Local Excitation Global Inhibition model, described in amoeba, where symmetry breaking arises from a local positive feedback (PIP3 that promotes F-actin polymerization) combined to a globally active diffusible inhibitory signal (PTEN, a PIP3 phosphatase) (3234).…”
Section: Discussionmentioning
confidence: 99%
“…Forces from the cellular environment are usually encountered primarily at the surface of the cell, where the force-generating cytoskeleton can also apply stresses as it comes into contact with various mechanical conditions. The adhesion complexes that connect cells to ambient tissues by focal adhesions and to other cells by adherens junctions have consequently been found to be key hubs in the transmission of forces ( Leckband and de Rooij, 2014 ; Seetharaman et al, 2021 ; Sun et al, 2016 ). There are, however, a much wider spectrum of mechanosensors inherent in cells, comprising several structurally diverse families of force-sensitive ion channels ( Kefauver et al, 2020 ) and receptors for biochemical ligands that react in a direct manner to force, such as notch ( Stassen et al, 2020 ) and plexin ( Mehta et al, 2020 ).…”
Section: Regulation Of Cellular Constituents Focal Adhesion Cytoskele...mentioning
confidence: 99%